Case Report: Surgery and genetic analysis of a complete androgen insensitivity syndrome family with testicular malignant tumors - Jiang, Lu; Jia, Peng; Duan, Baofeng; Zhang, Yan (Frontiers in Genetics, 2023)
Complete androgen insensitivity syndrome (CAIS) is a rare sex development disorder that results from X-linked androgen receptor gene mutations. Malignant transformation of the gonads is the most feared complication in postpubertal patients. In the current report, primary amenorrhea, infertility, and groin mass were symptoms described by a 58-year-old woman and his younger sister. Their two aunts, who shared the same clinical traits, passed away for an unknown reason. After gonadectomy, both patients were diagnosed with seminoma and an extratesticular benign tumor, and the elder sister suffered from breast cancer about a year after the operation. The diagnosis of CAIS was verified by whole-exome sequencing (WES), in which an uncommon mutation (c.2197G>A) in the AR gene was identified. This is the first family report of CAIS with germ cell tumors. The identified AR gene mutation based on WES can expand the understanding of CAIS.